2020
DOI: 10.3390/ijms21051853
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and Water Handling in the Medaka Intestine: A Possible Role of Claudin-15 in Paracellular Absorption?

Abstract: When euryhaline fish move between fresh water (FW) and seawater (SW), the intestine undergoes functional changes to handle imbibed SW. In Japanese medaka, the potential transcellular aquaporin-mediated conduits for water are paradoxically downregulated during SW acclimation, suggesting paracellular transport to be of principal importance in hyperosmotic conditions. In mammals, intestinal claudin-15 (CLDN15) forms paracellular channels for small cations and water, which may participate in water transport. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…As the aqp genes are downregulated in the medaka intestine after SW transfer [ 139 ], the decreased cldn15 expression in SW may be related to increased water permeability of the paracellular route (see 4.2.1). Recently, Tipsmark et al [ 234 ] suggested that CLDN15 in the medaka intestine may be water-permeable because the density of immunoreactive CLDN15 at TJs did not change in SW despite downregulation of cldn15 transcripts.…”
Section: Future Directionsmentioning
confidence: 99%
“…As the aqp genes are downregulated in the medaka intestine after SW transfer [ 139 ], the decreased cldn15 expression in SW may be related to increased water permeability of the paracellular route (see 4.2.1). Recently, Tipsmark et al [ 234 ] suggested that CLDN15 in the medaka intestine may be water-permeable because the density of immunoreactive CLDN15 at TJs did not change in SW despite downregulation of cldn15 transcripts.…”
Section: Future Directionsmentioning
confidence: 99%
“…In euryhaline fish, the change between fresh and saltwater conditions leads to adaptive changes to allow the handling of the imbibed seawater [ 42 ]. In the fish intestine, transcellular aquaporin-dependent water transport is downregulated, and paracellular transport via the two paralogs of claudin-15 present in fish, cldn15a and cldn15b, plays a major role.…”
Section: Tight Junctions Sense and React To Environmental Conditiomentioning
confidence: 99%